2016
DOI: 10.1038/bdjteam.2016.156
|View full text |Cite
|
Sign up to set email alerts
|

Why are vulnerable children not brought to their dental appointments?

Abstract: A considerable number of children with an oral healthcare need under 16 years of age are not brought to their Barts Health Special Care Community Dental Service (BHSCCDS) appointments. The BHSCCDS needed to understand more about why parents/ carers (parents) were failing to bring their children, in order to identify appropriate strategies to reduce the non-attendance.Thus, an audit was conducted to assess the number, frequency and reasons for all missed appointments (MA); this included feedback conversations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…2 Special needs and vulnerable children would also greatly benefit from this simple yet cost-effective approach. 3 G. Pettit, Adelaide DOI: 10.1038/sj.bdj.2015.763…”
Section: The Word From Down Under Whole Mouth Healthmentioning
confidence: 99%
“…2 Special needs and vulnerable children would also greatly benefit from this simple yet cost-effective approach. 3 G. Pettit, Adelaide DOI: 10.1038/sj.bdj.2015.763…”
Section: The Word From Down Under Whole Mouth Healthmentioning
confidence: 99%
“…In 2012, the British Dental Association issued the individual booklets Oral healthcare in prisons and secure settings for England, Scotland and Wales where many of the ongoing issues in prison dentistry were highlighted. 3 …”
Section: Unheard Voices Behind Barsmentioning
confidence: 99%
“…Their findings, set out in a consultation document, 2 identify a long-standing increasing incidence of infective endocarditis across the world, not just in the UK. A close reading of the NICE consultation document shows their analysis of the recent paper by Dayer et al, 3 which triggered the review. They found that it overestimated the increase in infective endocarditis incidence since 2008, failed to show any causal link to dental treatment and was at high risk of bias.…”
Section: Guideline Comment Infective Endocarditismentioning
confidence: 99%
See 1 more Smart Citation